Hydrogen peroxide enhances the efficacy of photodynamic therapy against Candida albicans biofilms - Viana de Sousa, Tábata [UNESP]; Carolina Jordão, Cláudia [UNESP]; Augusto Abreu-Pereira, César [UNESP]; Gorayb Pereira, Ana Luiza [UNESP]; Barbugli, Paula Aboud [UNESP]; Klein, Marlise Inêz; Pavarina, Ana Claudia [UNESP] (Taylor & Francis, 2023)
The present study aimed to evaluate the effectiveness of hydrogen peroxide (H2O2) combined with antimicrobial photodynamic therapy (aPDT) on biofilms formed by Candida albicans strains which are either susceptible to or resistant to fluconazole. Biofilms were grown and treated with H2O2, followed by the application of Photodithazine® (P) and red light-emitting diode (LED) (L) either separately or combined (n = 12). After the treatment, biofilms were evaluated by estimating colony-forming unit ml−1, extracellular matrix components [water -soluble and -insoluble polysaccharides, proteins, extracellular DNA (eDNA)], biomass (total and insoluble dry-weight), and protein concentration. Biofilms formed by both strains presented a significant reduction in cell viability, biomass, extracellular matrix components (both types of polysaccharides, eDNA), and proteins (in the soluble and insoluble portion of biofilms) compared to the control. Microscopy images of the biofilms after treatments showed disarticulation of the matrix and scattered fungal cells. The application of H2O2 can disturb the organization of the extracellular matrix, and its association with aPDT potentiated the effect of the treatment.
Keywords: Candida albicans; hydrogen peroxide; Photochemotherapy